Evaluating lactate metabolism for prognostic assessment and therapy response prediction in gastric cancer with emphasis on the oncogenic role of SLC5A12 - Lin, Chenyi; Ye, Jianjian; Xu, Chao; Zheng, Ying; Xu, Yining; Chen, Yuluo; Chi, Liangjie; Lin, Jia; Li, Feng; Lin, Yao; Wang, Qingshui (Biochimica et biophysica acta. General subjects, 2025)
Gastric cancer remains a common malignancy with poor prognosis. While lactate metabolism is recognized as a significant factor in tumor progression, its potential as a predictive tool for treatment response remains unexplored. This study introduces a novel Lactate-Related Gene Signature (LRGS) designed to predict both survival outcomes and therapy responses in gastric cancer patients. We comprehensively analyzed 335 lactate-related genes from 11 metabolic pathways using MSigDB, identifying 278 differentially expressed genes between gastric cancer and normal tissues. Employing the LASSO Cox regression model, we developed an innovative LRGS formula based on the expression of 16 key lactate-related genes. The impact of Solute Carrier Family 5 Member 12 (SLC5A12), a gene of particular interest, on gastric cancer cell functions was evaluated using in vitro assays and an in vivo zebrafish model. Our newly established LRGS demonstrated robust capability in stratifying gastric cancer patients by survival risk. Notably, the LRGS-low subtype showed significantly improved overall and disease-free survival rates compared to the LRGS-high subtype. A key finding was LRGS's ability to predict patient responses to both adjuvant chemotherapy and immunotherapy. Random forest analysis identified SLC5A12 as the most significant gene differentiating gastric cancer from normal tissues. Functional experiments confirmed SLC5A12's role in promoting gastric cancer cell proliferation, invasion, and migration both in vitro and in vivo. The LRGS is a dependable and efficient prognostic tool for assessing the survival outcomes in individuals with gastric cancer, as well as a predictor of patient response to adjuvant chemotherapy and immunotherapy. •Developed an LRGS using 16 lactate-related genes to stratify gastric cancer patients by survival risk and treatment response.•Identified SLC5A12 as key in differentiating cancer and normal tissues; highlighted its role in promoting tumor progression.•Demonstrated LRGS's prognostic and therapeutic value, reinforcing lactate metabolism's role and targeting SLC5A12 in cancer.